PROTECTIVE EFFECTS OF TRIMETAZIDINE AGAINST DOXORUBICIN-INDUCED CARDIOTOXICITY AND HEPATOTOXICITY IN MICE - Sikandar, Abeera; Farhat, Kulsoom; Afzal, Ayesha; Ajmal, Khalida; Laeeq, Mehwish; Khokhar, Aamna (Journal of Ayub Medical College Abbottabad, 2020)
Background: Trimetazidine (TMZ) is traditionally known for cardio protection, however various experimental studies are also evaluating its protective benefits in other tissues. Doxorubicin (DOX) is an extensively used chemotherapeutic drug but is associated with a high incidence of multi-organ damage. This study was aimed at countering DOX induced cardiac and hepatic toxicity by administering TMZ in two different study designs. Methods: It was a laboratory based randomized controlled trial conducted on 40 BALB/c mice divided into 5 groups (n=8). In the two study designs conducted, TMZ in a dose of 10 mg/kg was given orally for five and ten consecutive days. On the third and eighth day of the respective designs, 10 mg/kg DOX was administered intraperitoneally. Results: DOX induced significant elevation of four biochemical markers, namely creatine kinase MB (CKMB), lactate dehydrogenase (LDH), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (p-value ‰¤0.0001). Histological changes in heart were graded to be moderate while hepatic changes were graded as mild. Trimetazidine administration for ten days attenuated the enzyme upsurge significantly with p-value ‰¤0.05 for ALT and ‰¤0.0001 for AST, LDH and CKMB. However, five-day TMZ administration caused nonsignificant restoration in ALT and CKMB level (p-value >0.05). Hepatic and cardiac histological changes were restored accordingly in both groups. Conclusion: Treatment with TMZ for ten days, seven of which were prior to DOX administration, was concluded to be an effective strategy to counter cardiac and hepatic toxicity of DOX. Keywords: Alanine aminotransferase; Aspartate aminotransferase; Cardiotoxicity; Creatine Kinase MB; Hepatotoxicity; Lactate Dehydrogenase; Trimetazidine